(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Analyzing language through the linguistic corpus and researching the ways and laws of its learning is one of the achievements in today’s field of linguistics. The aim of this article is to increase the number of these achievements by one more by bringing innovation to computer linguistics. Also, the article presents the structure and functions of the software of the morphological dictionary of the Uzbek language, the importance of the software, user-friendly and effective aspects of computer linguistics will be highlighted in the educational process.